Monitoring the evolution and benefits of responsible research and innovation Summarising insights from the MoRRI project - EC; Stilgoe, Jack; Peter, Viola; Jäger, Angela; Madsen, Emil B; Woolley, Richard; Mejlgaard, Niels; Bloch, Carter; Bührer, Susanne; Wuketich, Milena; Lena Tsipouri; Meijer, Ingeborg; et al. (Publications Office of the European Union, 2018)
Monitoring the evolution and benefits of Responsible Research and Innovation (RRI) in Europe has been a three-and-a-half year-long endeavour in terms of conceptual thinking, data challenges, pragmatic solutions, critical reflections and last but not least substantial findings. The study programme started with an initial scoping of the RRI dimensions (Gender equality, Public engagement, Science literacy and science education, Open access, Ethics, and as overarching dimension Governance). A heavy data collection exercise - including the collection of existing data and the launch of different surveys - was complemented by 蠰ڌ糰ڈtoring the Evolution and Benefits of Responsible Research and Innovation (MoRRI) was a project tasked with implementing a monitoring system for responsible research and innovation (RRI) across its five dimensions (gender equality, science literacy and science education, public engagement, ethics, open access/open data), and governance. In addition to identifying indicators for the evolution of RRI, it identified social, democratic, economic and scientific benefits of RRI, and also conducted preliminary work to lay out routes towards implementing impact indicators. This is the final report of the MoRRI project. It provides details of all aspects of the work carried out, analysis of the data collected, and insights and reflections obtained during the course of the project.